Legal Status and Cross-Border Transport in Carbon Capture and Storage (CCS): an International and Indonesian Law Perspective - Prayudi, Hening Cipta Putih W; Arifin, Shofiana Nurul; Putri, Adela Oktaviani; Karuniawan, Andrea (Universitas Islam Sultan Agung, 2025)
This study analyzes the legal status and cross-border transportation of carbon in Carbon Capture and Storage (CCS) under international and Indonesian law. Indonesia’s commitment to net-zero emissions by 2060 has encouraged CCS adoption, regulated by Presidential Regulation No. 14 of 2024, which permits foreign carbon storage through bilateral agreements. While offering economic opportunities, this framework also presents legal and environmental risks, especially regarding the unclear classification of carbon across jurisdictions. The regulation does not define carbon’s legal status, leaving a gap that may cause differing interpretations with partner countries. Domestic inconsistencies are also reflected in Minister of Trade Regulation No. 84 of 2019, which permits only the import of specific non-hazardous wastes, from which carbon is excluded, thereby creating potential conflict with CCS policies. Using normative legal research with statutory and comparative approaches, this study reviews Indonesian provisions against international instruments such as the London Protocol, Basel Convention, and OSPAR 1992. Findings show that carbon in CCS technically qualifies as waste, but international law provides exceptions for climate mitigation, which Indonesia has not yet adopted. This legal gap, compounded by inconsistencies between environmental and trade regulations, may hinder the implementation of cross-border CCS. The study contributes novelty by assessing carbon’s legal classification and its implications for Indonesia’s role as a CCS host country. It recommends enacting explicit national rules, harmonizing domestic provisions with international standards, and ratifying the London Protocol Amendment to ensure legal certainty, environmental integrity, and sustainable CCS implementation.